Informação: do tratamento ao acesso e utilização - Tálamo, Maria de Fátima Gonçalves M.; Cintra, Anna Maria Marques; Kobashi, Nair Yumiko; Lara, Marilda Lopes Ginez de (Comunicação & Educação, 1994)
In modern society, information constitutes an object of first-need. Such as knowledge, accumulated knowledge takes place as a result of the search for the largest amount of information on a certain subject. It is necessary to have criteria which allow us to classify and systematize information, making it an object of specific learning. Therefore, it is necessary to know how to use documentary language.